Can credit quality as a moderating variable in increasing profitability: study on conventional commercial banks listed on the Indonesia stock exchange - Sriyono Sriyono; Ana Nabellah (Jurnal Siasat Bisnis, 2022)
Purpose: Increasing Profitability is necessary for a business so that business activities can still exist. Many previous studies have examined this matter. However, none have used credit quality as a moderating variable. This study aims to determine whether credit quality can be moderated to increase profitability.Methodology: The population used is Conventional Commercial Bank Companies listed on the Indonesia Stock Exchange. The sample of this research is 80 conventional commercial bank companies listed on the Indonesia Stock Exchange. The sampling technique uses purposive sampling—data analysis using Partial Least Square with Smart PLS 3.0 software.Finding: The result found a relationship between Capital Adequacy Level, Credit Distribution, Credit Quality, and Profitability. It showed that the level of capital adequacy has a positive effect on profitability. Credit quality cannot moderate the relationship between capital adequacy and lending to profitability.Research limitation/Implication: This research was only conducted on conventional banks listed on the Indonesian stock exchange. The variables studied are only limited to financial factorsPractical Implication: The management will understand that the strategy to increase profitability does not require credit quality support through the research results. The use of moderating variables is expected to provide a new model for increasing profitabilityOriginality: In increasing profitability, the researcher offers a new model by using credit quality as a moderating variable.Keywords: Capital Adequacy Level, Credit Distribution, Profitability, Credit Quality.